Development of a liquid chromatography-mass spectrometry method to investigate branched chain amino acid and acylcarnitine metabolism in type 2 diabetes - Pabla, Pardeep (2021)
The global prevalence of obesity and type 2 diabetes (T2D) continues to rise at an alarming rate. Despite the well-established association between obesity and an increased risk of developing T2D, the mechanisms underlying the pathogenesis of T2D with obesity remain unclear. Skeletal muscle is a major site for the disposal of ingested carbohydrate in healthy individuals. It is generally accepted that chronic overnutrition leads to accumulation of fat and fatty acid metabolites within the skeletal muscle which are believed to play a pivotal role in the progression of insulin resistance to carbohydrate metabolism which is one of the pathological hallmarks of T2D. Whilst several metabolites have been implicated, there appears to be no consensus over which metabolite is mediating skeletal muscle insulin resistance.